Locally pressed fibre Bragg grating pressure sensor - Correia, Ricardo N.; Chehura, Edmon; James, Stephen W.; Tatam, Ralph P. (Cranfield University, 2006)
A spectral-hole created by locally pressing a fibre Bragg grating exhibited a wavelength-shift within the FBG bandwidth. A sensitivity of 74.3pm/(N/mm) was obtained for pressure applied along the slow axis of a high birefringence fibre.